2023
DOI: 10.2174/1871527320666210618103344
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines and Sleep Architecture: A Systematic Review

Abstract: Background: Insomnia, defined as a difficulty in initiating or maintaining sleep, is a relevant medical issue. Benzodiazepines (BZDs) are commonly prescribed to treat insomnia. Two phases characterize human sleep structure: sleep with Non-Rapid Eye Movement (NREM) and sleep with Rapid Eye Movement (REM). Physiological sleep includes NREM and REM phases in a continuous cycle known as “Sleep Architecture.” Objective: This systematic review summarizes the studies that investigated BZDs changes on Sleep Archit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…We found that KS patients still presented a lower proportion of REM sleep than AUD patients but did not differ any more from controls. This finding is in accordance with the literature [ 65 ], which indicates a reduction in time spent in REM sleep associated with the use of benzodiazepines. However, most KS patients receive psychotropic medications in their usual living conditions, which implies that the present findings reflect the clinical reality of KS patients [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 93%
“…We found that KS patients still presented a lower proportion of REM sleep than AUD patients but did not differ any more from controls. This finding is in accordance with the literature [ 65 ], which indicates a reduction in time spent in REM sleep associated with the use of benzodiazepines. However, most KS patients receive psychotropic medications in their usual living conditions, which implies that the present findings reflect the clinical reality of KS patients [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 93%
“…Benzodiazepines have acute sedative and anxiolytic effects ( Konopka and Zimmerman, 2014 ). Taken acutely or chronically, these agents also impact the expression of the homeostatic sleep system, altering sleep architecture ( Holbrook et al, 2001 ; Ribeiro de Mendonça et al, 2021 ). Within the circadian system, benzodiazepines can produce major shifts in the endogenous rhythm ( Turek and Van Reeth, 1988 ) and can also impact entrainment to light ( Van Reeth and Turek, 1987 ).…”
Section: Exogenous Stimuli That Affect Masking Behaviormentioning
confidence: 99%
“…We were unable to obtain detailed data on the studies that pooled depressive and anxiety disorders. Furthermore, only two of the selected studies ( 20 , 21 ) took into account the potential interaction of benzodiazepine and/or antidepressant medication in the relationship between sleep and anxiety, despite their wide prescription in anxiety disorders (and particularly among anxious patients presenting sleep disorders) and the well-documented effects of these drugs on sleep architecture ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%